Green HRM Strategies and Their Impact on Managerial Effectiveness: Insights from IT Firms Across India (Journal of Informatics Education and Research, 2025)
Through the identification and analysis of crucial Green HRM (Green Human Resource Management) practices relevant to the IT industry throughout PAN India, this study offers a fresh step forward in the pursuit of sustainability. By exploring these practices, the study seeks to offer a comprehensive knowledge of how HR methods unique to the IT industry include sustainability goals. The study also looks at how these important Green HRM practices affect manager performance and retention. In IT firms operating throughout PAN India, the key goal is to evaluate how integrating green initiatives into HR activities affects managers' decisions to stay with their companies and improves their overall work performance. A questionnaire distributed to managers in the IT sector was used to collect data for the study, and AMOS was used for structural equation modeling (SEM) analysis. The results highlight the necessity for enterprises to take a comprehensive approach that takes into account both the motivational and knowledge components of green behavior. Such a strategy guarantees that members are not only knowledgeable about and equipped to participate in sustainable practices, but also continue to be inspired to support and align with the company's environmental objectives.